2012
DOI: 10.1007/s11250-012-0107-3
|View full text |Cite
|
Sign up to set email alerts
|

Effect of mastitis during the first lactation on production and reproduction performance of Holstein cows

Abstract: The aim of this study was to evaluate the effect of postpartum mastitis between first calving and subsequent conception on production and reproduction performance as well as culling of Holstein cows. A data set of 9,183 first lactation cows was used. Results showed that the first cumulative 100 days' milk production and the milk yield standardized to 305 days were affected by the interval from calving to first mastitis (P<0.05). Cows with one episode of mastitis produced more milk than those with repeated epis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 21 publications
0
12
0
Order By: Relevance
“…Because exact information could not be confirmed after multiple attempts to contact the authors, this manuscript was excluded. For 8 manuscripts (Vaarst and Enevoldsen, 1997;Sviland and Waage, 2002;Gasqui et al, 2003;Heringstad et al, 2006;Wolfová et al, 2006;Wolf et al, 2010;Heravi Moussavi et al, 2012;Oliveira et al, 2013), ancillary information regarding CM description (e.g., number of cow lactations or cow days followed) was missing. Authors of the 8 manuscripts were contacted and asked to provide the needed information; this information was obtained for 3 manuscripts (Sviland and Waage, 2002;Gasqui et al, 2003;Heringstad et al, 2006) and was not available for 1 manuscript (Oliveira et al, 2013), and an answer from the authors could not be obtained for 4 manuscripts (Vaarst et al, 2002;Wolfová et al, 2006;Wolf et al, 2010;Heravi Moussavi et al, 2012).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Because exact information could not be confirmed after multiple attempts to contact the authors, this manuscript was excluded. For 8 manuscripts (Vaarst and Enevoldsen, 1997;Sviland and Waage, 2002;Gasqui et al, 2003;Heringstad et al, 2006;Wolfová et al, 2006;Wolf et al, 2010;Heravi Moussavi et al, 2012;Oliveira et al, 2013), ancillary information regarding CM description (e.g., number of cow lactations or cow days followed) was missing. Authors of the 8 manuscripts were contacted and asked to provide the needed information; this information was obtained for 3 manuscripts (Sviland and Waage, 2002;Gasqui et al, 2003;Heringstad et al, 2006) and was not available for 1 manuscript (Oliveira et al, 2013), and an answer from the authors could not be obtained for 4 manuscripts (Vaarst et al, 2002;Wolfová et al, 2006;Wolf et al, 2010;Heravi Moussavi et al, 2012).…”
Section: Resultsmentioning
confidence: 99%
“…In 4 studies (Rajala and Gröhn, 1998;Sviland and Waage, 2002;Monti and de Jong, 2005;Pérez-Cabal et al, 2009), CM data were obtained from existing databases; all other studies used prospective CM data collection. Regarding the minimal lag time between CM episodes to consider them as independent episodes, 3 studies (Gasqui et al, 2003;Pérez-Cabal et al, 2009;Heravi Moussavi et al, 2012) used a minimum of only 1 d between CM episodes in their case definition. Minimal number of days between CM events used in the other studies ranged from 5 d (Wolf et al, 2010) to 21 d (Rajala and Gröhn, 1998).…”
Section: Systematic Review and Meta-analysis On Risk Of CM Recurrencementioning
confidence: 99%
“…Moussavi et al . [25] reported that more episodes of mastitis in early lactation significantly increased the SC with no apparent impact on the DO. Interestingly, we also observed that cows in the first and second parities diagnosed with CM had significantly delayed DTFDH.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, in vitro studies developed in cattle have shown the anti-inflammatory effect of meloxicam in mammary epithelial cells (25). Furthermore, mastitis in cows has been associated with reduced pre-weaning immunity, growth, and health of the offspring (26,27), so the anti-inflammatory effect elicited by meloxicam treatment is presumed to have the opposite effect.…”
Section: Transfer Of Passive and Active Immunitymentioning
confidence: 99%